Retinal Pigment Epithelial Detachment in Age-Related Macular Degeneration - Michael Karampelas; Panagiotis Malamos; Petros Petrou; Ilias Georgalas; Dimitrios Papaconstantinou; Dimitrios Brouzas (Ophthalmology and Therapy, 2020)
Abstract Retinal pigment epithelial detachment is defined as a separation of the retinal pigment epithelium from the inner collagenous layer of Bruch’s membrane. It is a common manifestation in both dry and wet types of age-related macular degeneration. This review aims to provide a comprehensive guide to the pathophysiology, clinical and imaging characteristics, natural course and treatment of the various types of pigment epithelial detachments in order to assist in diagnosis and management of this important feature of age-related macular degeneration.